Utilizing Quizizz for Game-Based Learning in Elementary Science Education - MY, Nurfadila; Hajar, Sitti; Arsyad, Nur Fajar (Journal of Education and Computer Applications, 2024)
This study investigates the utilization of Quizizz, a game-based learning platform, in elementary science education. The research aims to assess the effects of integrating Quizizz on student engagement, academic performance, and retention of scientific concepts. Employing a qualitative approach, a systematic literature review was conducted to explore educators' and students' experiences with Quizizz in the context of elementary science education. The research design entailed thematic analysis of existing literature to identify recurrent patterns and insights related to game-based learning, Quizizz, and elementary science education. Data collection involved gathering and synthesizing information from scholarly sources, including academic journals and conference proceedings. The analysis revealed several key findings: Quizizz enhances student engagement and motivation, fosters collaborative learning, and promotes inquiry-based learning. Moreover, Quizizz is effective in improving students' academic performance and comprehension of scientific concepts. The study contributes to the existing knowledge base by providing evidence-based recommendations for educators seeking to leverage technology-enhanced learning tools in elementary science education.